The arrival of a second ‘Lessepsian sprinter’? A first record of the red cornetfish Fistularia petimba in the Eastern Mediterranean - STERN, NIR; PAZ, GUY; YUDKOVSKY, YANA; LUBINEVSKY, HADAS; RINKEVICH, BARUCH (Mediterranean Marine Science, 2018)
Here we document the first occurrence of the red cornetfish Fistularia petimba in the Levantine Basin. This species identity has been confirmed using morphological and molecular tools, and is presented here with simplified illustrations for accurate future identification. This report voices a concern regarding another blitz invasion of a cornetfish into the Mediterranean, following its Lessepsian sprinter congeneric, F. commersonii, one of the most efficacious invaders of the Mediterranean Sea. The wide intra-specific genetic distances found between sympatric F. petimba specimens in the available literature resources may also demonstrate the presence of cryptic diversity within this taxon.